Analisis Kesantunan Berbahasa terhadap Komentar Pembaca Berita Terkait Virus Corona - Dwi Nur Ishlah; Slamet Triyadi; Dewi Herlina (Jurnal Bahasa dan Sastra, 2022)
This research is motivated by the popularity of the Corona virus news in Indonesia, at this time the world is being hit by a very terrible outbreak, namely the corona virus. If you look at the news of the Corona virus in online media, the information uploaded generally invites comments and various responses from readers, causing the emergence of speech forms that violate the principles of politeness in language. Therefore, this study aims to describe compliance and violations of language politeness contained in the comments column related to the Corona virus in the Kompas.com Instagram account. This study uses a qualitative approach with a descriptive method. The data collection technique used is the listening technique and the note-taking technique, namely by listening to the use of language and collecting data by noting important things that can produce meaning to complete this research study. Furthermore, the data were analyzed using descriptive analysis techniques, descriptive analysis techniques, namely a study that is not limited to data collection, by including analysis and interpretation of the data itself. The results of the research on the analysis of language politeness using Leech's theory contained in this study include the maxim of wisdom, generosity, praise, humility, agreement, and the maxim of sympathy. The findings of this study indicate that based on the results of data analysis, it was found that compliance with the principles of politeness in language is more dominant than violations of the principles of politeness in language.